A young man presenting with paralysis after vigorous exercise. (27th August 2012) - Gubran, Christopher; Narain, Rajay; Malik, Luqmaan; Saeed, Saad Aldeen
Abstract : Thyrotoxic periodic paralysis (TPP) is a rare metabolic disorder characterised by muscular weakness and paralysis in predisposed thyrotoxic patients. Although patients with TPP are almost uniformly men of Asian descent, cases have been reported in Caucasian and other ethnic populations. The rapid increase in ethnic diversity in Western and European nations has led to increase in TPP reports, where it was once considered exceedingly rare. Correcting the hypokalaemic and hyperthyroid state tends to reverse the paralysis. However, failure to recognise the condition may lead to delay in diagnosis and serious consequences including respiratory failure and death. We describe a young man who was diagnosed with hyperthyroidism who presented with acute paralysis. The clinical characteristics, pathophysiology and management of TTP are reviewed.